Étude sur les besoins spécifiques des femmes immigrantes francophones en situation minoritaire - Alliance des femmes de la francophonie canadienne (L’Alliance des femmes de la francophonie canadienne (AFFC), 2021)

Stratégies d’intégration et de support en santé mentale des immigrants francophones au Canada anglais. - Archambault, Hélène; de Moissac, Daniel; Tempier, Raymond (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Résumé Cet article explore les stratégies d’intégration au système de santé telles que proposées par des personnes immigrantes francophones au sein de communautés francophones en situation minoritaire au Canada (CFSM). Une recherche qualitative par entrevues semi-dirigées a été menée dans trois villes canadiennes auprès de soixante personnes adultes immigrantes ou réfugiées. Centrées sur les représentations des personnes immigrantes quant aux services de soutien en santé mentale, diverses stratégies ont été dégagées. La préparation prémigratoire et le regroupement des informations sous un guichet unique semblent contribuer à une intégration réussie. L’appui des organismes communautaires et des autorités religieuses est bénéfique pour le soutien informationnel et socioémotionnel des nouveaux arrivants, ayant des retombées positives sur leur bien-être et leur capacité de s’intégrer à leur nouveau milieu de vie. Mots-clés : immigration, francophones, intégration, système de santé, stratégies Abstract This article explores healthcare integration strategies proposed by Francophone immigrants within Francophone minority communities (FMCs) in Canada. A qualitative study using semi-structured interviews was conducted in three Canadian cities with sixty adult immigrants and refugees. Focusing on immigrants’ perceptions of mental health support services, various strategies were identified. Pre-migration preparation and centralizing information seem to contribute to successful integration. The support of community organizations and religious authorities is beneficial for the socio-emotional and information support of newcomers, having a positive impact on their well-being and their ability to integrate into their new living environment. Keywords: immigration, Francophones, integration, healthcare, strategies

Newcomers and social and health pressures in Franco-Manitoban communities: Overview of avenues of research and preliminary considerations - Bahi, Boniface (Canadian Issues, 2008)
This article outlines theoretical considerations and preliminary data for a research project undertaken at the request of the research office at the Collège universitaire de Saint-Boniface in Winnipeg, with the support of the Corporation Catholique de la Santé du Manitoba. The Corporation's "Étude d'évaluation stratégique sur l'intégration des médecines alternatives à la médecine officielle (2006-2009)" seeks to build the capacities of public medical institutions in view of, among other things, socio-demographic changes caused by the arrival of newcomers. The study, now in progress, is already concerned with the potential clientele for the alternative health services that would be integrated into what is regarded as officiai medicine. Our research project, entitled "Nouveaux arrivants et pathologies émergentes en milieu franco-manitobain: Quelles exigences?" seeks to identify newcomers' implicit (unexpressed) and explicit (known) demands regarding sociocultural and health services available in the Franco-Manitoban host community. The first step involves collecting basic data on migration trends and their multidimensional implications at the community level. This article will, therefore, focus on contrasting local social and health services with the direct and indirect demands of newcomers. It will attempt to identify requirements for community, social and institutional development. The abovementioned theoretical considerations relate to the issues, objectives and approach of our research project. The preliminary data consist of information obtained from Accueil francophone and from several immigrants, such as the excerpt at the beginning of this paper.

An analysis of crisis services accessibility of new francophone arrivals in the city of Winnipeg - Buissé, Diane M.N. (University of Manitoba, 2005)

Accès aux services sociaux et de santé en français : l’expérience des Franco-Manitobains - de Moissac, Danielle; Giasson, Florette; Roch-Gagné, Margaux (Minorités linguistiques et société / Linguistic Minorities and Society, 2015)
Des progrès considérables sont constatés dans l’offre de services et la formation de professionnels dans le domaine des services sociaux et de santé en français au Manitoba depuis les 30 dernières années. L’objectif de cette recherche est de mieux connaître la perception des usagers quant aux services couramment disponibles et aux barrières réduisant l’accès à ces services. L’obtention de services en français est importante pour la population francophone, particulièrement pour les aînés et les immigrants. En moyenne, 50 % des répondants disent demander des services en français, mais seulement 25 % affirment les recevoir. La pénurie de professionnels pouvant offrir des services en français est considérée comme la barrière principale à l’accès. L’offre active est essentielle et facilite la prestation des services dans la langue de choix de la clientèle. Mots-clés : accessibilité, santé, services sociaux, Manitoba, minorité francophone

Barriers to HIV care among Francophone African, Caribbean and Black immigrant people living with HIV in Canada: A protocol for a scoping systematic review - Djiadeu, Pascal; Nguemo, Joseph; Mukandoli, Chantal; Odhiambo, Apondi. J.; Lightfoot, David; Mbuagbaw, Lawrence; Nelson, LaRon. E. (BMJ Open, 2019)
Introduction Language is a social determinant of health. Addressing social determinants of health is paramount to successful progression along the HIV-care continuum. Canada is a bilingual country with French and English as official languages. There are few studies to date that have focused on the impact of being a French-speaking linguistic minority on the HIV-care continuum. The primary objective of this scoping, systematic review of literature is to evaluate existing gaps in access to HIV- care among French-speaking people living with HIV in Canada. Our primary outcome is healthcare services availability and access for French- speaking people living with HIV. Methods and analyses Our scoping, systematic review will draw on a systematic search of published literature, both quantitative and qualitative studies published on French-speaking individuals' healthcare and HIV status in Canada, with particular emphasis on the province of Ontario. We will conduct our search in MEDLINE, the Excerpta Medica Database, the Cumulative Index to Nursing and Allied Health Literature, Web of Science, EBSCO and Google Scholar for work published between 1990 and 2018. Identified articles will be screened in duplicate and full-text articles of relevant studies will be retrieved. Data will also be extracted by two researchers working independently. Any discrepancies that arise will be resolved by consensus or by consulting a third author. Our findings will be reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Ethics and dissemination Our proposed research will not be conducted with human participants. We will only use secondary published data and therefore ethics approval is not required. Our findings will be disseminated as peer reviewed manuscripts at conferences and student rounds, and could be of interest to government health agencies and local HIV/AIDS service organisations.

Barriers in accessing HIV care for Francophone African, Caribbean and Black people living with HIV in Canada: A scoping review - Djiadeu, Pascal; Yusuf, Abban; Ongolo-Zogo, Clémence; Nguemo, Joseph; Odhiambo, Apondi J.; Mukandoli, Chantal; Lightfoot, David; Mbuagbaw, Lawrence; Nelson, LaRon. E. (BMJ Open, 2020)
Introduction In 2001, 50%–55% of French-speaking minority communities did not have access to health services in French in Canada. Although Canada is officially a bilingual country, reports indicate that many healthcare services offered in French in Anglophone provinces are insufficient or substandard, leading to healthcare discrepancies among Canada’s minority Francophone communities. Objectives The primary aim of this scoping systematic review was to identify existing gaps in HIV-care delivery to Francophone minorities living with HIV in Canada. Study design Scoping systematic review. Data sources Search for studies published between 1990 and November 2019 reporting on health and healthcare in Francophone populations in Canada. Nine databases were searched, including Medline, Cumulative Index to Nursing and Allied Health Literature, the Cochrane Library, the National Health Service Economic Development Database, Global Health, PsychInfo, PubMed, Scopus and Web of Science. Study selection English or French language studies that include data on French-speaking people with HIV in an Anglophone majority Canadian province. Results The literature search resulted in 294 studies. A total of 230 studies were excluded after duplicates were removed. The full texts of 43 potentially relevant papers were retrieved for evaluation and data extraction. Forty-one studies were further excluded based on failure to meet the inclusion criteria leaving two qualitative studies that met our inclusion criteria. These two studies reported on barriers on access to specialised care by Francophone and highlighted difficulties experienced by healthcare professionals in providing quality healthcare to Francophone patients in Ontario and Manitoba. Conclusion The findings of this scoping systematic review highlight the need for more HIV research on linguistic minority communities and should inform health policymaking and HIV/AIDS community organisations in providing HIV care to Francophone immigrants and Canadians.

Repérage de quelques obstacles linguistiques et culturels des soins de santé pour les immigrants francophones de la Nouvelle-Écosse - Fontaine, Louise (Port Acadie, 2010)
Ce texte s’attarde au concept d’« immigrant francophone » appliqué au contexte de la Nouvelle-Écosse. Contrairement à ce qu’on peut imaginer à un premier niveau d’analyse, ce concept est polysémique et le sens qu’on y attribue varie selon les acteurs sociaux qui l’utilisent. Donc, afin de mieux délimiter l’objet de notre propos, nous avançons quelques éléments de définition à prendre en compte. Il s’agit d’une recherche exploratoire orientée vers la formulation de quelques pistes de réflexion, voire quelques hypothèses de travail à vérifier lors de la réalisation de futures recherches dans le domaine de la santé auprès des communautés francophones et acadiennes de la Nouvelle-Écosse. Pour étoffer notre propos, nous présentons quelques données empiriques recueillies à même le travail de terrain mené principalement dans le milieu associatif à Halifax et dans le sud-ouest de la province depuis 2003. Dans ce contexte, nous avons mené des enquêtes en procédant notamment à de l’observation participante. Nous avons aussi eu recours à des documents écrits tels que des documents gouvernementaux, des articles dans des revues spécialisées, des journaux. Les liens que nous avons établis entre des thèmes comme langue, culture et santé nous ont conduite finalement à proposer quelques questions de recherche et quelques hypothèses de travail.

Iniquités de santé en milieu minoritaire : diagnostic de la situation chez les immigrants francophones de Sudbury - Hien, Amélie; Lafontant, Jean (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectif Cet article vise à mettre au jour des iniquités de santé liées non seulement au fait de vivre dans un milieu linguistique minoritaire, mais aussi au fait d’être immigrant et de vivre dans un nouvel environnement avec une culture d’origine différente de celle de sa communauté d’accueil. Méthode Il s’agit d’une étude qualitative qui présente les expériences personnelles de nombreux immigrants francophones dans leurs rapports aux services et aux soins de santé à Sudbury ainsi que leurs perceptions quant à la qualité et l’accessibilité de ces services et soins. Soixante-douze (72) individus âgés de 18 à 65 ans, dont 45 hommes et 27 femmes, ont participé à cette recherche à travers des entrevues individuelles et des groupes de discussions. Résultats Les résultats obtenus montrent, entre autres, qu’être immigrant et francophone limite l’accès aux services de santé, affecte la qualité de ces services et nuit à une prise en charge efficace des problèmes de santé. C’est ainsi que certains individus ne sont même pas en mesure de donner un consentement éclairé lors de décisions importantes à prendre concernant leur santé. Conclusion L’article fait des suggestions pour que ces immigrants puissent accéder à de meilleurs services et soins de santé, en vue de contribuer à l’amélioration de la santé de la population canadienne dont ils sont partie intégrante.

Vers des services attirants, accessibles et pertinents pour les personnes âgées immigrantes francophones ? - Nduwimana, Mathilde; Home, A. (Reflets, 1995)
Cet article décrit et analyse les besoins et préoccupations des personnes âgées autonomes appartenant aux groupes ethniques francophones et résidant dans Ottawa-Carleton. L'objectif principal est d'explorer les raisons pour lesquelles elles utilisent peu les services de soutien communautaires pour les personnes âgées francophones. Nous avons effectué des entrevues semi-structurées auprès de quatre représentantes et de six personnes âgées des communautés ethno-culturelles francophones, et nous avons effectué une analyse de contenu par thème. Les répondantes ont souligné les besoins de contacts sociaux, d'apprentissage du français et/ou de l'anglais, d'accès aux moyens financiers adéquats et d'information sur les ressources disponibles. Des obstacles liés au contexte socio-écono-politique dans la société d'accueil entravent la satisfaction de ces besoins. La levée de certaines barrières concrètes, la modification des politiques sociales et des pratiques d'intervention faciliteraient l'accès aux services par les personnes âgées des groupes ethniques francophones et augmenteraient leurs options.

Experiences of French speaking immigrants and non-immigrants accessing health care services in a large Canadian city - Ngwakongnwi, Emmanuel; Hemmelgarn, Brenda. R.; Musto, Richard; Quan, Hude; King-Shier, Kathryn. M. (International Journal of Environmental Research and Public Health, 2012)
French speakers residing in predominantly English-speaking communities have been linked to difficulties accessing health care. This study examined health care access experiences of immigrants and non-immigrants who self-identify as Francophone or French speakers in a mainly English speaking province of Canada. We used semi-structured interviews to gather opinions of recent users of physician and hospital services (N = 26). Language barriers and difficulties finding family doctors were experienced by both French speaking immigrants and non-immigrants alike. This was exacerbated by a general preference for health services in French and less interest in using language interpreters during a medical consultation. Some participants experienced emotional distress, were discontent with care received, often delayed seeking care due to language barriers. Recent immigrants identified lack of insurance coverage for drugs, transportation difficulties and limited knowledge of the healthcare system as major detractors to achieving health. This study provided the groundwork for future research on health issues of official language minorities in Canada. Keywords: immigrants; French language; health care access; family doctor; qualitative descriptive; official language minorities

Misinterpretation: Language proficiency, recent immigrants, and global health disparities - Pottie, Kevin (Canadian Family Physician, 2007)

Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.

Processus de développement d’une trousse d’accompagnement pour l’examen médical des nouveaux arrivants francophones : un exemple de coopération - Sanou, Boroma; Beaudoin, Monique; Gauthier, Alain P.; Chomienne, Marie-Hélène; Prud’homme, Denis; Kpazaï, Georges (Revue de la Diversité de la Recherche en Santé, 2020)
While over the half of Francophone immigrants living in Ontario come from Africa and the Caribbean, Canadian-trained health professionals are not sufficiently familiar with the health problems that newcomers may face. With this in mind, in a multi-disciplinary partnership, the Center for Rural and Northern Health Research, the Centre de santé communautaire du grand Sudbury, l’Institut du savoir Montfort, the School of Human Kinetics at Laurentian University, and a group of French-speaking immigrants from the City of Greater Sudbury, developed using a collaborative research approach, a newcomer’s medical examination toolkit for health professionals and social services. The toolkit development process involved several steps: 1) establishing a partnership between the above-mentioned organizations; 2) literature review to identify the most common health problems; 3) selection of the most common problems that are not necessarily those that health professionals encounter in everyday practice; 4) writing of draft versions with emphasis on some important aspects of the disease; 5) validation of the fact sheets by the partners; 6) the restitution of the final fact sheets (25 fact sheets including 3 on the general examination, 10 related to certain tropical diseases, 8 sheets related to the signs and symptoms most frequently encountered by health professionals and the other 4 on health care in Ontario); and 7) the development of a digital infograph to ensure greater visibility of the Toolkit for the medical examination of Francophone newcomers.

Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil - Sanou, Boroma; Gauthier, Alain P.; Hien, Amélie; Michel, Isabelle; Timony, Patrick (Centre de recherche en santé dans les milieux ruraux et du nord, 2020)

Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil. Principaux résultats du rapport technique - Sanou, Boroma; Gauthier, Alain P.; Hien, Amélie; Michel, Isabelle; Timony, Patrick (Santé Canada et Consortium national de formation en santé - Volet Larentienne et Volet Boréal, 2020)

Potential for patient-physician language discordance in Ontario - Sears, Jennifer; Khan, Kamran; Ardern, Chris . I.; Tamim, Hala (BMC Health Services Research, 2013)
Background Patient-Physician language discordance occurs when the patient and physician lack proficiency in the same language(s). Previous literature suggests language discordant clinical encounters compromise patient quality of care and health outcomes. The objective of this study was to quantify and visualize the linguistic and spatial mismatch between Ontario’s population not proficient in English or French but proficient in one of the top five non-official languages and the physicians who are proficient in the same non-official language. Methods Using data from the 2006 Canadian census and the 2006 Canadian Medical Directory, we determined the number of non-English/non-French (NENF) speaking individuals and the number of Ontario physicians proficient in the top five non-official languages in each census division (CD) of Ontario. For each non-official language, we produced bi-variate choropleth maps of Ontario, broken down into the 49 CDs, to determine which CDs had the highest risk of language discordant clinical encounters. Results According to the 2006 Canadian census, the top five non-official languages spoken by Ontario’s NENF population were: Chinese, Italian, Punjabi, Portuguese and Spanish. For each of the top five non-official languages, there were at least 5 census divisions with a NENF population speaking a non-official language without any primary care physicians proficient in that non-official language. The size of NENF populations within these CDs ranged from 10 individuals to 1,470 individuals. Conclusions Understanding the linguistic capabilities of Ontario’s immigrant population & the linguistic capabilities of Ontario’s primary care physicians is essential to ensure equal access and quality of healthcare. As immigration continues to increase, we may find that the linguistic needs of Ontario’s immigrant population diverge from the linguistic capabilities of Ontario’s primary care physicians. Further research on the language discordance in Ontario is needed in order to reduce the risk of language discordant clinical encounters and the negative health outcomes associated with these encounters.

Pratique # 27 : Accueil centralisé (Centre francophone du Grand Toronto, Ontario) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (2025)

Access to healthcare services and confidence in healthcare professionals’ management of malaria: the views of Francophone sub-Saharan African Immigrants living in western Canada - Vincent, Rémi; Coulibaly, Kongnon Sangué; Ahmed, Ali; Ahmed, Youssef; Hanna, Taylor A.; Ravi, Srilata; Hawkes, Michael T.; Gnidehou, Sedami (BMC Public Health, 2023)
Abstract Background There is a paucity of knowledge about the healthcare attitudes and practices of French-speaking immigrants originating from Sub-Saharan Africa (FISSA) living in minority settings. The purpose of this study was to characterize FISSA healthcare experiences and confidence in the malaria-related knowledge of health professionals in Edmonton. Methods A structured survey was used to examine a cohort of 382 FISSA (48% female; 52% male) living in Edmonton. FISSA general healthcare attitudes, experiences and satisfaction with the Canadian healthcare system were studied. Healthcare Competency Perception (HCP) was characterized by using an index score. Statistical analyses were performed to evaluate the impact of healthcare experiences and other outcomes. Results Intriguingly, while only 42% of FISSA had a French-speaking family physician, 83% (197/238) of those who had received health care services in Alberta found that access to medical treatment was easy, and 77% (188/243) were satisfied with received care. Although 70% (171/243) of FISSA did not receive services in French, 82% (199/243) surprisingly reported having good levels of comprehension during their visits. Satisfaction with care was associated with having a family physician (p = 0.018) and having health insurance (p= 0.041). Nevertheless, confidence in the healthcare system’s ability to treat malaria effectively was significantly lower, with only 39% (148/382) receiving a positive score on the HCP index. Conclusion This study provides an important insight into FISSA experience with and perception of the Alberta’s healthcare system.

Construction of Francophone families’ health literacy in a linguistic minority situation - Zanchetta, Margareth. Santos; Kaszap, Margot; Mohamed, Mohamed; Racine, Louise; Maheu, Christine; Masny, Diana; Cèsar, Ines; Maltais, Claire; Sangwa-Lugoma, G.; Lussier, Nancy; Kinslikh, Diana (Alterstice, 2012)
With the  increase  in  international  mobility,  healthcare  systems  should  no  longer  be  ignoring  language  barriers.  In  addition  to  the  benefit  of  reducing  long‐term  costs,  immigrant‐friendly  organizations  should  be  concerned  with  mitigating  the  way  language  barriers  increase  individuals’  social  vulnerabilities  and  inequities  in  health  care  and  health  status.  This  paper  reports  the  findings  of  a  qualitative,  exploratory  study  of  the  health  literacy  of  28  Francophone  families  living  in  a  linguistic‐minority  situation  in  Canada.  Analysis  of  interviews  revealed  that  participants’  social  vulnerability,  mainly  due  to  their  limited  social  and  informational  networks,  influenced  the  construction  of  family  health  literacy.  Disparities  in  access  to  healthcare  services  could  be  decreased  by  having  health  professionals’  work  in  alliance  with  Francophone  community  groups  and  by  hiring  bilingual  health  professionals.  Linguistic  isolation  and  lack  of  knowledge  about  local  cultural  organizations  among  Francophone immigrants  were  two  important  findings  of  this  study.